The Comparison of Sukuk and Bond Absorption; Deficit Budget Financing in Indonesia - salman al parisi; Aam Slamet Rusydiana (Tazkia Islamic Finance and Business Review, 2016)
Objectives: This study aims to analyze: (i) the comparison of sukuk and bond absorption in deficit budget financing; and (ii) which variable that has significant effect on deficit budget (Y1= equation 1), on bond (Y2= equation 2) and on sukuk (Y3 = equation 3).Method: This study uses Two Stage Least Square (2SLS) method. The data used is from Bank of Indonesia, BPS, Ministry of Finance, IDX, ministry of trade, with monthly data, February 2009 – December 2015.Results: The result shows that sukuk has a significant negative effect on deficit budget while bond has a significant positive effect on deficit budget. In addition, import has a significant negative effect on deficit budget while exchange rate variable has a significant positive effect on deficit budget (the first equation). BI rate has significant negative effect on bond, while SBI and deficit budget has significant positive effect on bond (the second equation). Then, Inflation and bond has significant positive effect on sukuk, while deficit budget has significant negative effect on sukuk (the third equation).Conclusion: Both sukuk and bond have significant correlation in increasing each of them. Furthermore, both sukuk and bond have significant effect on deficit budget.